The Use of Translanguaging in Bilingual Class: A Study of Perception on the Students at An Islamic Junior High School - Antika, Rindi; Jabu, Baso; Sakkir, Geminastiti (Yayasan Cendekiawan Indonesia Timur, 2026)
While translanguaging is increasingly recognized as a pedagogical tool, its implementation in the specific context of Islamic bilingual junior high schools remains under-explored, particularly from the students' perspective. This study investigates how students at SMP IT Al-Biruni Mandiri Jipang perceive and interpret translanguaging in their bilingual classrooms. Using a descriptive qualitative approach, data were gathered through three days of classroom observations and in-depth interviews with six seventh-grade students, then analyzed using the interactive model of Miles and Huberman (1994). The findings reveal that students perceive translanguaging as a vital